The pawnbroker [videorecording (DVD)] - Lumet, Sidney, 1924-2011; Steiger, Rod, 1925-2002; Peters, Brock; Sánchez, Jaime, 1938-; Hernandez, Juano; St. Jacques, Raymond, 1930-1990; Fitzgerald, Geraldine, 1913-2005; Jones, Quincy, 1933-; Wallant, Edward Lewis, 1926-1962 (Republic Entertainment ; Distributed by Artisan Home Entertainment, 2003)
A long time ago, Sol Nazerman was a professor. He had a wife, children. Then the Germans came. Sol survived the concentration camp, his family did not. Now, as the pawnbroker in a shop owned by a racketeer, he grows increasingly bitter and callous, withdrawing still further from the world around him. His eager assistant Jesus looks to him as both a teacher and a father figure, but Sol eschews involvement or compassion. This detachment leads to a tragedy, which awakens Sol's humanity, wherein he can finally acknowledge his burden of grief and guilt.